Entrepreneurial Character Formation within Families and Its Implications for Community Empowerment - Nur Amang Rustang; Ni Luh Sinta Yani; Puji Novita Sari (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study examines the formation of entrepreneurial character within families and its broader impact on community development. Using a qualitative research approach, data were collected through observations, in-depth interviews, questionnaires, and documentation involving 43 respondents from a family-based community setting. Data were analyzed through systematic qualitative procedures to capture patterns of entrepreneurial character formation and its perceived outcomes. The findings reveal that families play a central role in cultivating core entrepreneurial values, including perseverance, discipline, high motivation, honesty, commitment, cooperation, leadership, responsibility, and risk-taking behavior. These values are deeply embedded in daily family practices and contribute to the sustainability of economic activities within the community. However, several entrepreneurial traits remain underdeveloped, particularly creativity, innovation, independence, communication skills, and curiosity, which may limit further entrepreneurial growth. In terms of impact, the formation of entrepreneurial character within families contributes positively to improved household welfare, job creation, skill enhancement, and the establishment of a more harmonious and resilient community. This study highlights the strategic importance of family-based entrepreneurial education as a foundation for long-term community empowerment and inclusive economic development.